Special tax regimes for sportsmen = Systemy opodatkowania sportowców - Szwajdler, Paweł (Journal of Education, Health and Sport, 2015)
Szwajdler Paweł. Special tax regimes for sportsmen = Systemy opodatkowania sportowców. Journal of Education, Health and Sport. 2015;5(4):374-379. ISSN 2391-8306. DOI 10.5281/zenodo.29033 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A374-379 https://pbn.nauka.gov.pl/works/611688 http://dx.doi.org/10.5281/zenodo.29033 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 30.04.2015. Special tax regimes for sportsmen Systemy opodatkowania sportowców Paweł Szwajdler Nicolaus Copernicus University in Toruń E-mail: szwajdli@onet.eu Abstract The main purpose of this work is to show diversity of tax regimes for sportsmen. The author focuses on tax regulations in Germany and in France. In this work is showed, that not only tax regimes, which are applicable to all sportsmen, are in force, but also regimes, which are applicable only to sportsmen who are non- residents. Author of this article is going to answer , if it is necessary to treat sportsmen in other way than other taxpayers. In this work, the author analyses legal regulations and specialist literature. Key words: taxation of sportsmen, tax regimes for sportsmen, taxes. Streszczenie Głównym celem niniejszej pracy jest wskazanie na różnorodność systemów opodatkowania sportowców. Autor skupia się przede wszystkim na regulacjach obowiązujących we Francji oraz w Niemczech. W pracy zostało wskazane, że specyficzne systemy opodatkowania sportowców dzielą się na konstrukcje prawne dotyczące wszystkich sportowców oraz na rozwiązania jurydyczne mające zastosowanie tylko do nierezydentów. Autor odpowiada w niniejszym artykule na pytanie, czy istnieją powody, dla których sportowcy powinny być opodatkowani w sposób odmienny, niż pozostali podatnicy. W pracy zastosowana została metoda polegająca na analizie tekstów prawnych oraz poglądów doktryny. Słowa kluczowe: opodatkowanie sportowców, systemy opodatkowania sportowców, podatki.